Effectiveness of Erector Spinae Plane Block for Postoperative Analgesia in Modified Radical Mastectomy (Community Based Medical Journal, 2022)
Postoperative pain control in breast cancer surgery has become one of the most important goals for anesthesiologists. Several techniques have been trialed for providing postoperative analgesia after breast surgery. This randomized control study was designed to evaluate the postoperative analgesic effect of ultrasound-guided erector spinae plane (US-guided ESP) block for modified radical mastectomy surgery. To evaluate the postoperative analgesic effect of pectoral nerves block and erector spinae plane block for modified radical mastectomy surgery. This prospective, randomized, controlled trial was conducted at the Department of Anaesthesia, Analgesia, Palliative & Intensive Care Medicine in Dhaka Medical College and Hospital. A total 46 patients who were to undergo modified radical mastectomy, fulfilling selection criteria were included in the study following confirmation of the informed written consent and randomly divided into two groups- where each group include 23 Patients. Group A received ultrasound guided ESP and group B received ultrasound guided PECS block. All patients of both groups received GA after confirmation of block. All relevant information including demographic criteria, medical history, clinical evaluation during and after performance of block were collected. All patients were observed peri-operatively and data were recorded into the preformed questionnaires form. Finally, data was analyzed by SPSS version 22.0. Mean age of study population was 52.07±7.08 years with majority in age group 50-59 years. No significant difference was noted between patient’s characteristics, duration of surgery and heart rate and mean arterial pressure of patient during and after operation between two groups (p>0.05). The mean VAS score was significantly low in ESP block as compared to the PECS block at all-time interval (p